The effect of different soft-tissue management techniques for alveolar ridge preservation: a randomized controlled clinical trial - Papace, Colline Maria; Büsch, Christopher; Ristow, Oliver; Keweloh, Martin; Hoffmann, Jürgen; Mertens, Christian (International journal of implant dentistry, 2021)
For alveolar ridge preservation, various treatment protocols have been described. While most studies focus on the effect of the bone graft material, the aim of this study was to analyze the influence of different soft-tissue management techniques on the soft and hard tissue.